Checkpoint Maths 2 - "Pimentel, Ric" (Hodder Education: London, 2011)
This new edition has been completely revised to match the new Cambridge Checkpoint tests, the new Cambridge Progression Tests for stage 8, and the Cambridge Secondary 1 curriculum frameworks
Keywords: Mathematics-Textbook